Fostering Academic Interdisciplinarity: Italy's Pioneering Experiment on Sustainability Education in Schools and Universities - Fioramonti, Lorenzo; Giordano, Claudia; Basile, Francesco Luca (Frontiers in Sustainability, 2021)
The world needs a systemic transformation from a social, economic and environmental point of view in order to deal with present and future challenges, which are crosscutting in nature. Education and research can become powerful drivers for this radical change, provided they can break free from narrow disciplinary approaches and cultivate the interconnectedness of knowledge. With a view to repurposing teaching and research towards an integrated approach, Italy has introduced a number of reforms, including a mandatory module for all schools and an interdisciplinary course for universities, largely modelled on the interdisciplinary concept of sustainability. Italy was the first country in the world to do so and the news had resonance throughout the globe, indicating a thirst for innovative methods in education and research. This article discusses the approach and the obstacles faced, with the aim of encouraging debate over its structure and contents and potentially replicating its implementation in other parts of the world.